The Protective Effects of γ-Tocotrienol on Muscle Stem Cells Through Inhibiting Reactive Oxidative Stress Production - Yang, Shuo; Yang, Juan; Zhao, Huiwen; Deng, Rong; Fan, Hancheng; Zhang, Jinfu; Yang, Zihao; Zeng, Huihong; Kuang, Bohai; Shao, Lijian (Frontiers in Cell and Developmental Biology, 2022)
Pseudotrophic muscular dystrophy is a common clinical skeletal muscle necrotic disease, among which Duchenne muscular dystrophy (DMD) is the predominant. For such diseases, there is no clinically effective treatment, which is only symptomatic or palliative treatment. Oxidative stress and chronic inflammation are common pathological features of DMD. In recent years, it has been found that the pathophysiological changes of skeletal muscle in DMD mice are related to muscle stem cell failure. In the present study, we established a DMD mice model and provided tocotrienol (γ-tocotrienol, GT3), an antioxidant compound, to explore the relationship between the physiological state of muscle stem cells and oxidative stress. The results showed that the application of GT3 can reduce ROS production and cellular proliferation in the muscle stem cells of DMD mice, which is beneficial to promote the recovery of muscle stem cell function in DMD mice. GT3 treatment improved the differentiation ability of muscle stem cells in DMD mice with increasing numbers of MyoD+ cells. GT3 application significantly decreased percentages of CD45+ cells and PDGFRα+ fibro-adipogenic progenitors in the tibialis anterior of DMD mice, indicating that the increased inflammation and fibro-adipogenic progenitors were attenuated in GT3-treated DMD mice. These data suggest that increased ROS production causes dysfunctional muscle stem cell in DMD mice, which might provide a new avenue to treat DMD patients in the clinic.